Respuestas
Respuesta dada por:
2
Solución:
Utilizar : Apotema = √(lado² - (lado/2)²)
4 = √(lado² - (lado/2)²)
4² = lado² - (lado/2)²
4² = lado² - lado²/4
4² = 3 × lado²/4
lado² = 4² × 4/3
lado² = 4² × 2²/3
lado = 4 × 2/√3
lado = 8/√3
lado = 8 × √3/(√3 × √3)
lado = 8√3/3 cm
Utilizar : Apotema = √(lado² - (lado/2)²)
4 = √(lado² - (lado/2)²)
4² = lado² - (lado/2)²
4² = lado² - lado²/4
4² = 3 × lado²/4
lado² = 4² × 4/3
lado² = 4² × 2²/3
lado = 4 × 2/√3
lado = 8/√3
lado = 8 × √3/(√3 × √3)
lado = 8√3/3 cm
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años